A Family Clustered Nitrite Intoxication Investigation in Gaoxin District, Suzhou, China, 2013. - Ruiping Wang; Chengang Teng; Ning Zhang; Jun Zhang; George Conway (Tehran University of Medical Sciences, 2013)
In April, 2013, a Suzhou Hospital reported a nitrite intoxication patient in coma as well as 2 family members with the similar symptom 5 days ahead. We investigated the event to identify the cause, source and possible pollution ways of the contamination.We defined case as any person living in YSHY community who has cyanosis and with at least one of the following symptoms: dizziness, headache, fatigue, tachycardia, drowsiness, nausea, vomiting, abdominal pain or diar-rhea during April 15 to April 25, 2013. We searched for case by interviewing community residents and reviewing clinics' medical records; information was then retrospectively collected on the patient's food history, cooking procedures and food sources.We identified 3 nitrite intoxication cases, 1 male and 2 female from a family. The interval time between dinner and onset was < 1 hour. Retrospective survey showed 'sugar stir and mix asparagus' on April 17 and 'scrambled asparagus' on April 21 were suspected foods. Both suspected dishes had 'sugar' added, sourced from a clean-up of a neighboring rental house. Nitrite was detected in a vomitus sample, the 'sugar' and two leftover food samples.This family clustered nitrite intoxication was induced by using unidentified nitrite as sugar to cook dishes. We recommend sodium nitrite should be dyed with bright colors to avoid mistaking it for plain salt or sugar, health departments strengthen food hygiene propaganda to improve people's recognition of food safety, and to alert them the dangerous of eating unidentified or unknown source food.